Hepatotoxicity in Indigenous Sheep of Malaysia Stall-fed with Different Forms of Brachiaria Decumbens - Othman, Abas Mazni; Haron, Sharif (1988)
Eighteen Indigenous Sheep were assigned to three treatment groups. They were stall-fed ad libitum with either (I) hay (II) green grass or (III) litter of Brachiaria decumbens mixed with copra cakes and molasses. The trial was conducted to determine whether hepatotoxicity will occur with the above method of feeding. After two weeks, five of six sheep in each group, I and II showed varying degrees of jaundice and mild photo sensitization. Marked elevation of SCOT and SCCT concentration were observed in these animals, indicating liver damage. Liver damage occured much earlier in sheep on hay than those fed green B. decumbens. Hence, this trial suggests that total feeding of B. decumbens to sheep either in the form of green grass or hay may cause hepatotoxicity.